2023
DOI: 10.3390/healthcare11071041
|View full text |Cite
|
Sign up to set email alerts
|

“Sex Should Not be Part of the Lives of Persons with Disabilities, but They Are Human Beings too”: Perceptions of Healthcare Providers and Factors Affecting Service Delivery in Ghana

Abstract: Persons with disabilities (PwDs) constitute about 16% of the global population and face many challenges in every society, including access to sexual and reproductive healthcare. The attitudes of healthcare providers (HPs) exert a major influence on PwDs accessing sexual and reproductive healthcare (SRH). A sequential explanatory mixed methods design was used to investigate the attitudes and perceptions of HPs towards PwDs and SRH delivery in Ghana’s Ashanti region. Quantitative data analysis indicated that ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Exclusion criteria were: a) under 18 years old, b) multiple disabilities, c) disabilities other than physical or visual impairment, and d) refusal to participate. More details regarding the study area and the inclusion and exclusion criteria can be found in previous studies [ 28 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria were: a) under 18 years old, b) multiple disabilities, c) disabilities other than physical or visual impairment, and d) refusal to participate. More details regarding the study area and the inclusion and exclusion criteria can be found in previous studies [ 28 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, outcomes consist of self-reported SRH issues among PwDs, including STIs, unintended and unwanted pregnancies, pregnancy termination, unsafe abortion, self-rated SRH, and experience of violence or abuse [ 42 ]. The model has been previously applied and explained in detail [ 28 , 43 ]. The rationale for using this framework for the current study is that it captures the complex and multifaceted factors influencing the sexual experiences, behaviour, and reproductive health outcomes of PwDs.…”
Section: Introductionmentioning
confidence: 99%
“…The study focused on those with visual/seeing (4%) and physical impairment/walking (3.6%) which were the most common types of disabilities in this area, with more PwDs living in urban (9.5%) than rural (6.5%) areas. Details of the study area have been published elsewhere [ 38 ]. The inclusion criteria for participant selection were (a) being 18 years or older, and (b) having either physical or visual impairment.…”
Section: Methodsmentioning
confidence: 99%
“…System characteristics pertain to the organization of systems, such as hospitals or healthcare provider networks, and their interactions, which collectively shape an individual's health [ 37 ]. A diagram showing the various components of the model and its detailed description have previously been published [ 38 , 39 ]. This current study focused specifically on three aspects of the framework: system characteristics, client characteristics, and interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation